Duke University School of Medicine New Students, October 1951 (1951)
Duke University School of Medicine New Students, October 1951: Asbill, D.P., Jr.; Bell, N.H.; Bennet, P.C., Jr.; Bercovitz, M.C.; Bethune, W.M., Jr.; Bilogan, R.M.; Bjerk, E.M., Jr.; Blum, L.M.; Bourland, W.L.; Bramlett, C.W.; Breibart, S.; Britt, B.E.; Bynum, R.S.; Carver, D.H.; Chamberlin, F.H.; Combs, J.J., Jr.; Cowan, D.E.; Cronland, M.A.; Crowder, T.H.; Cupp, H.B., Jr.; David, A.K., Jr.; Deyton, R.G., Jr.; Dukes, H.T.; Farmer, J.L., Jr.; Fox, N.A., Jr.; Gore, J.P.; Gore, T.W.; Goswick, C.B.; Graham, F.W., Jr.; Haim, L.; Hilgartner, M.W.; Hutchin, P.P.; Ira, G.H., Jr.; James, J.; James, R.E.; Jelks, A.N.; Johnson, H.W.; Johnston, C.C., Jr.; Jones, E.L.; Kinneman, R.E., Jr.; Lang, W.S., Jr.; Langley, J.T.; Langstaff, Q.A.; Lipton, H.P.; McAuley, E.R.; McCall, B.W.; Merwarth, C.R.; Mitchell, D.C.; Murphey, W.C.; Neal, C.B.; Ocker, J.M., Jr.; Pagter, A.T., Jr.; Pierce, J.A.; Rankin, W.; Reeves, J.W., Jr.; Saunders, D.E., Jr.; Scherle, E.M.; Silver, D.; Simon, H.; Sledge, J.B., Jr.; Slocumb, M.B.; Smith, R.B.; Snow, J.W.; Soo, K.W.; Spanel, D.L.; Steagall, R.W., Jr.; Stillwell, E.F.; Stokes, T.A., Jr.; Strauss, S.; Tanaka, S.; Taylor, E.L., Jr.; Thames, T.B.; Watson, D.F.; West, B.C., Jr.; Wiggs, E.O.; Wiita, R.M.; Wilder, B.J.; Williams, D.S.; Young, J.M.; Young, W.M., Jr.